Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1007/s00784-021-04278-9
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of an FTO gene polymorphism in the temporomandibular joint osteoarthritis

Abstract: Objectives The FTO gene has been reported as an obesity-associated gene and is also considered a risk gene for osteoarthritis (OA). However, its exact function is unclear, and there is conflicting evidence on the involvement of FTO polymorphisms in OA via obesity. The purpose of this study was to determine the effects of FTO polymorphism rs8044769 alleles on OA in the temporomandibular joint (TMJ), which is minimally affected by body weight. Materials and methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 38 publications
1
5
0
Order By: Relevance
“…Panoutsopoulou et al examined the strength of association of rs8044769 with knee or hip OA (adjusted for gender) and detected a distinct association of the FTO variant with knee OA (OR 1.08 [95% CI 1.02-1.14], P = 0.009) rather than hip OA (OR 1.04 [95% CI 0.98-1.11], P = 0.17) in Caucasian populations. For nonweight-bearing joints such as hand and TMJ OA, FTO polymorphism also increased the OA risk (22,23). These findings require further validation in the future with larger-scale observational studies.…”
Section: Discussionmentioning
confidence: 92%
“…Panoutsopoulou et al examined the strength of association of rs8044769 with knee or hip OA (adjusted for gender) and detected a distinct association of the FTO variant with knee OA (OR 1.08 [95% CI 1.02-1.14], P = 0.009) rather than hip OA (OR 1.04 [95% CI 0.98-1.11], P = 0.17) in Caucasian populations. For nonweight-bearing joints such as hand and TMJ OA, FTO polymorphism also increased the OA risk (22,23). These findings require further validation in the future with larger-scale observational studies.…”
Section: Discussionmentioning
confidence: 92%
“…However, some argue that the causal relationship between obesity and OA is difficult to establish ( Pang et al, 2013 ), thus rejecting this theory. For example, compared patients with temporomandibular joint osteoarthritis (TMJOA)with the general population and concluded that the frequency of the FTO polymorphism allele was significantly different between the two groups, while the differences in weight, age, and sex were not statistically significant Takaoka et al (2022) . Yang et al found that lncRNA AC008 was highly expressed in human OA cartilage samples, and found that aberrant expression of AC008 affected OA progression by regulating chondrocyte viability, chondrocyte apoptosis and ECM degradation.…”
Section: N6-methyladenosine and Bone Developmentmentioning
confidence: 99%
“…In vivo, the obese mice fed high-fat diets presented with osteoarthritis-like changes and increased the expression of Interleukin-1 Beta (IL-1B), Matrix metalloproteinase-3 (MMP-3) and leptin in temporomandibular joints [ 13 ]. Moreover, the CC allele of rs8044769 in the FTO gene (an obesity-associated gene) is proved as a risk factor for temporomandibular joint osteoarthritis [ 16 ]. Conversely, patients with TMDs might have difficulty in food intake and tend to lose weight [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%